Pengembangan Sistem Penjualan Gelang Manik Hello Eunoia Menggunakan Strategi CRM Guna Meningkatkan Loyalitas Pelanggan - Wulandari, Maria Sri; Noveandini, Rahayu; Aningsih, Dewi Sifa (Universitas Multi Data Palembang, 2025)
Hello Eunoia is a creative industry that has been established since 2021. This industry sells handicraft products made from beads, especially bracelets. For sales and promotion techniques, Hello Eunoia wants to apply web-based information technology. This is because so far Hello Eunoia has only relied on social media with the WhatsApp, Instagram and manual face to face platforms. Therefore, it is necessary to create a web-based sales system for bead bracelets at Hello Eunoia using CRM (Customer Relationship Management) as a sales system for the Hello Eunoia creative industry to make it easier for sellers to communicate all forms of information both about products and shops to buyers, so that buyers can receive valid information conveyed via WhatsApp and email media. The development model used is System Development Life Circle (SDLC). The software used is Sublime Tex, Xampp, and Mysql. The tests carried out are black box testing, browser performance testing and Likert scale user testing. From the test results, the function and usability of this application can run well. This application can make it easier for customers to place orders and make transactions anytime and anywhere without having to come directly to the shop.